Peaceful kitchen : more than 100 cozy plant-based recipes to comfort the body and nourish the soul - Perez, Catherine (HarperOne, an imprint of HarperCollins Publishers, 2024)
From nutritionist and social media star @plantbasedrd, more than one hundred, nourishing, feel-good, and easy-to-follow recipes, inspired by Mexican and Dominican flavors, for mindful, creative plant-based meals. In her first cookbook, Catherine Perez, a food creator and registered dietitian, guides you through a delightful exploration of mouthwatering plant-based recipes, proving serenity can be found in a well-balanced, wholesome meal. Whether you are considering a plant-based diet, lead a dedicated vegan lifestyle, or just want some new ways to season and enjoy veggies, Peaceful Kitchen is for you. Perez helps you take the stress out of eating well with recipes that pull from the Mexican and Dominican dishes and flavors she was raised on--adding her own delicious twists--served with a side of the latest evidenced-based research. From Moro de Habichuelas to Breakfast Tostadas, she shows you how eating healthfully doesn't mean eating blandly. Inviting you into her own life, Perez inspires you to make the kitchen a true expression of yourself--bringing your own imagination, heritage, and fun to mealtime--so you can cultivate calm as you prepare mindful, sustainable meals. Discover meals like: Mangu Power Bowl with Crispy Adobo Chickpeas and Onions; Peach Upside-Down Baked Oatmeal; Spicy Peanut Shaved Brussels Sprout Salad; Tofu Tinga Taco; Wholesome Date and Pistachio Cookies; Dominican Sofrito; and so much more! With recipes that are both nostalgic and innovative, delicious and nutritious, flavorful and filling, Perez will reshape how you eat, one dish at a time, and help you turn the kitchen into your Zen space.